Applying Circular Economy to Regenerative Tourism on Island: Insights from Con Dao, Vietnam - Tuyen, Tran (CV. Literasi Indonesia, 2025)
The development of mass tourism in islands is encountering issues of resource depletion and overcapacity. Simultaneously, sustainable tourism models seek to mitigate adverse effects but do not entirely restore impacted destinations. Consequently, regenerative tourism grounded in a circular economy may serve as a viable solution to the challenges faced by islands. Con Dao, a small, ecological island in Vietnam facing significant environmental problems due to growing mass tourism, serves as a case study to explore the above integration. This paper aims to develop a regenerative tourism model based on the circular economy concept through field research and in-depth interviews with tourists, local officials, and tourism businesses. The results showed that the model is made up of three main domains: (1) a circular tourism value chain that makes the best use of resources and cuts down on waste; (2) circular and regenerative governance that encourages stakeholders to work together and makes sure that policies are aligned; and (3) regenerative tourism practices that encourage responsible behavior that is good for ecological recovery. This study also introduces specific techniques for each component to provide theoretical and practical contributions.